Legal Challenges of Asset Misappropriation in the Digital Era - Febriyani, Emiliya; Tantimin, Tantimin (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
The growing challenges of addressing asset misappropriation in Indonesia's digital era highlight the need for a thorough examination of the existing legal framework to assess its effectiveness and adaptability. This paper examines legal challenges of digital asset misappropriation in Indonesia. It explores the legal implications of asset misappropriation as a crime within the context of digital technology, analyzing current Indonesian legislation's adequacy in addressing these issues. Employing a normative legal research method and statutory approach, this research investigates relevant laws and regulations in Indonesia that can be used to criminalize asset misappropriation. In addition, this study employs a case approach by analyzing court decisions related to asset misappropriation, providing practical insights into how the legal framework is applied in real-world scenarios. Key findings suggest that while current Indonesian legislation addresses various aspects of asset misappropriation, it lacks specific provisions for the digital context. This gap necessitates a more holistic legal approach that integrates both traditional and digital environments, while also acknowledging the legal implications on digital aspects, namely data as the center of focus. Recognizing asset misappropriation as a distinct criminal offense can serve as a foundational step in criminalization efforts. This approach can then be integrated with existing legal provisions relevant to the digital environment, allowing perpetrators to be prosecuted under multiple dimensions of Indonesia's legal framework for more comprehensive enforcement.